2016
DOI: 10.13189/aeb.2016.041106
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of the Foreign Banks' Expansion in South Eastern Europe: Do Greek Banks Still Follow Their Customers Abroad or Not?

Abstract: The paper deals with the factors that led to the great penetration of Greek banking sector in South Eastern Europe during [2000][2001][2002][2003][2004][2005][2006][2007]. We investigate the validity of the follow the customer hypothesis. Based on the eclectic theory, after controlling for ownership advantages, we found that host country conditions, opportunities in the host financial markets and risk conditions are proved to be significant determinants. Our findings indicate that although follow the customer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…It was found that banks from developed economies seek to expand their scale and market and enhance their competitiveness by establishing overseas branches (Mastrapasqu, 1973; Petrou, 2007). In addition, the global expansion of banks from developed economies are also driven by the internationalization of their clients, which subsequently promotes banks to expand abroad (Chou & Shen, 2014; Fotopoulos et al., 2016). Compared to their Western counterparts, the expansion of banks from China had been limited over the past decades (Pan, He, Sigler, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that banks from developed economies seek to expand their scale and market and enhance their competitiveness by establishing overseas branches (Mastrapasqu, 1973; Petrou, 2007). In addition, the global expansion of banks from developed economies are also driven by the internationalization of their clients, which subsequently promotes banks to expand abroad (Chou & Shen, 2014; Fotopoulos et al., 2016). Compared to their Western counterparts, the expansion of banks from China had been limited over the past decades (Pan, He, Sigler, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%